Human Reliability Assessment (HRA) of Fire and Explosion Cases at Fuel Filling Stations (SPBU) - Tananta, Naufal Nizaar Halim; Ramadhani, Adhitya Ryan (MOTIVECTION : Journal of Mechanical, Electrical and Industrial Engineering, 2024)
Filling Stations are public facilities provided by fuel distributors for the fuel needs of the broader community that have serious potential risks, such as fires and explosions that human actions or systems can cause. This research aims to identify the causes of these errors, evaluate their likelihood, and provide recommendations to reduce them. This paper incorporated Fault Tree Analysis (FTA) and the Success Likelihood Index Method (SLIM). Data analysis identifies 16 basic events from 3 aspects: human, technical, and management, focusing on FTA. Notably, SLIM highlights error mode 3 (0.0392 probability) as the most critical, while error mode 4 is the least significant (0.000234). These methods provide recommendations to minimize human error, including training, Application of SOPs, incident report submission system, supporting technology, supervision, regular inspections, and audits.